A Critical Comparison of Conventional, Certified, and Community Management of Tropical Forests for Timber in Terms of Environmental, Economic, and Social Variables. Issue 1 (15th April 2016) - Burivalova, Zuzana; Hua, Fangyuan; Koh, Lian Pin; Garcia, Claude; Putz, Francis
Abstract: Tropical forests are crucial in terms of biodiversity and ecosystem services, but at the same time, they are major sources of revenue and provide livelihoods for forest‐dependent people. Hopes for the simultaneous achievement of conservation goals and poverty alleviation are therefore increasingly placed on forests used for timber extraction. Most timber exploitation is carried out unsustainably, which causes forest degradation. Two important mechanisms have emerged to promote sustainable forest management: certification and community‐based forest management (CFM). We synthesize the published information about how forest certification and CFM perform in terms of environmental, social, and economic variables. With the caveat that very few published studies meet the standards for formal impact evaluation, we found that certification has substantial environmental benefits, typically achieved at a cost of reduced short‐term financial profit, and accompanied by some improvement to the welfare of neighboring communities. We found that the economic and environmental benefits of CFM are understudied, but that the social impacts are controversial, with both positive and negative changes reported. We identify the trade‐offs that likely caused these conflicting results and that, if addressed, would help both CFM and certification deliver the hoped‐for benefits.